Derivation and validation of myocardial bridge characteristics by optical coherence tomography: a prospective multimodality imaging study. (14th October 2021) - Otsuka, T; Ueki, Y; Losdat, S; Baer, S; Raeber, L
Abstract: Background: Optical coherence tomography (OCT) findings of myocardial bridge (MB) have not been established. Purpose: We aimed to establish the OCT appearance of MB compared with the half-moon sign derived by intravascular ultrasound (IVUS) and to assess the prevalence among patients undergoing coronary angiography and OCT in clinical practice. Methods: For derivation of the OCT appearance of MB, imaging data obtained from 122 patients undergoing OCT and IVUS for the left anterior descending artery (LAD) enrolled in two prospective imaging studies were analyzed. To assess the prevalence of OCT-derived MB, 470 patients undergoing OCT for LAD in clinical routine were analyzed. Results: We found a homogeneous band with intermediate light intensity surrounding the vessel wall as assessed by OCT corresponding to half-moon sign derived by IVUS. Mean length, angle, and thickness of OCT-MB were 21.2±10.8mm, 205.7±56.5°, and 0.39±0.06mm, respectively. Mean length of IVUS-MB was significantly longer as compared with OCT-MB (23.7±11.9, P=0.010), while there were no significant differences in angle and thickness. MB angle was >180° in approximately 50% of frames with MB. There was a strong/moderate correlation between OCT-MB and half-moon sign (MB length: r=0.81, P=0.001, MB angle: r=0.58, P=0.001). In the derivation cohort, sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of OCT-MB for the milking effect by angiography were 96.3%, 62.1%, 41.9%, 98.3%, and 69.7%, respectively, and much comparable with the IVUS half-moon sign. In the validation cohort, OCT-detected MB was observed in 139 (29.6%) patients, of whom 57.6% (n=80) did not have angiographic evidence of milking effect. Conclusion: OCT is able to identify IVUS-defined MB as homogenous band with intermediate light intensity surrounding the vessel wall. There was a high concordance in terms of MB angle and thickness between OCT and IVUS. In clinically-indicated OCT cases of the LAD, more than half of OCT-MBs were angiographically silent. OCT assessment of MB may facilitate the accurate diagnosis of MB and thus provide useful information in determining the subsequent treatment strategy for the patients with MB. Funding Acknowledgement: Type of funding sources: None.